A New Generic Placement for “Calliostoma” Blakei Clench & Aguayo, 1938 (Gastropoda: Trochoidea) - Güller, Marina (2014)
“Calliostoma” blakei Clench & Aguayo, 1938, described from Río Negro Province, Argentina, appears in the literature either under the genera Calliostoma, Photinula (Calliostomatidae) or as a member of the Umboniinae (Trochidae). The study of live-collected specimens allows to revise its generic placement.The species is characterized by a bipectinate ctenidium with short afferent membrane, isolated appendices in the left side of the neck, and the rachidian and the first lateral teeth reduced to their base. This set of characters, not present in any other trochoid, leads us to propose the new genus Carolesia for this species.